An Investigation of the Performance of Cooperative Thrift and Credit Societies In Financing Small-Scale Businesses in Nigeria - Aribaba, Foluso Olugbenga (Mediterranean Journal of Social Sciences, 2013)
This study investigated the performance of Cooperative Thrift and Credit Societies in financing small-scale businesses andidentified the problems confronting CTCS in providing finances to small-scale businesses. This was with a view to providinginformation on the role of CTCS in the development and growth of small-scale businesses.Primary data involving theadministration of questionnaire was utilized for the study. The instrument elicited information on the socio-demographicbackground of the cooperative leaders and small-scale entrepreneurs, the sources of funds to CTCS, sources of financeavailable to small-scale businesses and problems encountered by the CTCS in financing small-scale business. Data collectedwere analysed using descriptive statistics.The result of the study showed that CTCS has performed creditably well in providingfunds to small-scale businesses. On the problems facing the CTCS in financing small-scale businesses of its members:inadequate fund (69.2%) and poor loan recovery (52.5%) were identified as the recurrent, while economic downturn (25.0%);bad leadership (15.8%); misappropriation of small-scale business capital (12.5%); poor accounting system (8.3%) and poorstate of infrastructure (4.2%) are regarded as other problems facing the CTCS in financing small-scale businesses. The studyconcluded that in general, membership of CTCS by entrepreneurs had a positive impact on the growth and development ofsmall-scale businesses in Nigeria.